The Usage of Banana Peels and Soybean Hull for the Treatment of Lake Water: Turbidity and Total Suspended Solids - Mohd Aripen, Nur Shahirah; Abdul Halim, Norhazimah; Saadon, Sabrina; Jamil, Nur Danisya Akma (Journal of Science and Technology, 2023)
Lake water get contaminate due to the growth of population and modernization which can causing problems. Therefore, it is crucial for wastewater to go through wastewater treatment to improves the quality of water. One of the processes involved is coagulation process. Chemical coagulants may have an adverse effect on the consumer and the environment. The use of natural coagulants can be a secure replacement for chemical coagulants. Hence, this study was conducted to reduce the usage of chemicals in the coagulation process by using natural coagulant of banana peels and soybean hulls. The main aim of this study is to investigate the effect of natural coagulant for wastewater treatment of lake water. Banana peels and soybean hulls were the main materials in making a plant-based coagulant by drying, grinding, and sieving. Jar test was carried out to investigate the effectiveness of natural coagulant by determining their turbidity and total suspended solids. It was found that banana peels perform effectively at a dosage of 400mg/L with turbidity removal achieved is almost 50%. On the other hand, soybean hulls work effectively at a dosage of 600mg/L with turbidity removal achieved is 54%.  Based on the result, it is shown that using banana peels as a natural coagulant has effectively reduced the turbidity and total suspended solids of lake water with the optimum number of dosages of 600mg/L.